Preparing Students for Globalization – Working with International Teams with Projects - Friesel, A. (Elektronika ir Elektrotechnika, 2010)
This paper summarizes the activities, contents and overall outcomes of our experiences with international students studying at the Copenhagen University College of Engineering (in short - IHK); in particular students coming for one semester exchange program under Erasmus-programme. IHK’s participation in EU-supported programmes like EIE-Surveyor and ELLEIEC, both ERASMUS thematic networks, have the positive influence on number of our partnership agreements with other European universities. Globalisation makes it necessary to cooperate on an international platform. At the IHK we have more than 50 active Erasmus agreements. We also have bilateral agreements with many non-European countries, for example: USA, China, Korea, Mexico, Chile and others. We describe our experiences of working on industrial projects with international teams and analyse the development and trends in student mobility. The growing popularity of these programmes and the increasing number of the students joining our international semesters demonstrates the success of this form of education. Equally, the growing number of projects coming from industry demonstrates their positive interest in these kinds of skills for their future employees.